Therapeutic effect of chinese herbal medicine gu-ben-hua-shi (AESS) formula on atopic dermatitis through regulation of yes-associated protein - Jia, Jinjing; Feng, Luyao; Ye, Siqi; Ping, Ruiyue; Mo, Xiumei; Zhang, Yu; Li, Xiong; Chen, Dacan (Frontiers in Pharmacology, 2022)
Background: Atopic dermatitis (AD) is a chronic and recurrent skin disease. At present, there is a lack of sufficiently effective and safe medicines that can be used for a prolonged time and reduce the recurrence of AD. The Gu-Ben-Hua-Shi (AESS) formula has been used for many years with a good clinical effect on AD but its specific treatment mechanism is unknown. Methods: The main components of AESS were analyzed using ultra-high performance liquid chromatography (UPLC). The composition of AESS compounds in the rats serum was analyzed using ultra-high performance liquid chromatography-mass spectrometry. An AD mouse model was constructed using 2,4-dinitrofluorobenzene stimulation in Balb/C mice and the effect on the reduction of skin lesions and Th1/Th2/Th17/Treg balance after AESS administration were measured. The effects of AESS on the proliferation and apoptosis of keratinocyte cell line HaCaT and adhesion of HaCaT to human monocyte cell line THP-1 were detected in an IFN-γ/TNF-α stimulated AD-like inflammatory cell model. The effects of Yes-associated protein (YAP) expression on the therapeutic effect and a related signaling pathway were also investigated. Results: In total, 10 components were confirmed using UPLC, namely five organic acids, three flavonoids, and two chromogenic ketones. Additionally, the similarity of the three batches of samples was above 0.98, indicating that the formula samples have good uniformity. These 10 compounds were also detected in rat serum, suggesting that they are absorbed into rat blood as prototype components. Furthermore, AESS effectively reduced the skin lesions in the AD mouse model, regulated the Th1/Th2/Th17/Treg imbalance, improved the proliferation ability of the AD-like cell model, and inhibited HaCaT apoptosis and adhesion to THP-1 cells. It also reduced the expression of YAP in Th17 and Treg cells of the mouse spleen and increased YAP expression in the skin. The change in YAP expression in keratinocytes weakened the curative effect of AESS, and AESS exerted its effects through the NF-κB signaling pathway. Conclusion: AESS may play a role in the treatment of AD by affecting the expression of YAP. These findings can be used to promote its use as an alternative medication for prolonged use with fewer side effects.